Toward Optimal Governance: Leveraging SIMDA for Enhanced Internal Control - Bachrudin K Una; Imanita Septian Rusdianti; Yusuf Adhi Prabowo; Novita Nurul Rohma; Ahmad Jainuri (Magister Akuntansi Universitas Pancasila, 2026)
Purpose: To evaluate the effectiveness of the implementation of the SIMDA Financial Application in financial management and reporting and its contribution to internal control at the BPKAD of Jayapura Regency. Considering the importance of internal control, this study focuses on measuring the effectiveness of the SIMDA Financial Application in supporting internal control. Methodology: A qualitative descriptive method using primary data obtained through interviews and document analysis. This data was then processed through data reduction, data presentation, and interpretation to gain a deeper understanding Findings: The implementation of the SIMDA Financial Application at the BPKAD Jayapura Regency has provided significant benefits. This application makes it easier to manage finances, from budgeting to reporting, delivering information and data accurately, effectively, and efficiently, as well as facilitating audits and coordination in policymaking. The implementation of SIMDA also allows better monitoring of public fund flows, reduces the risk of corruption, and makes it easier to make better decisions based on timely information. Implication: The implementation of SIMDA at BPKAD Jayapura Regency has the potential to improve internal control and the management of local government finances. By using information technology appropriately, SIMDA enables a more efficient, transparent, and accountable financial management process. This can help minimize human errors, boost operational efficiency, and better achieve the local government's strategic goals. In addition, implementing SIMDA also has the potential to create good governance based on the principles of transparency, accountability, and information security. Originality: This study examines the implementation of the Regional Financial Management Information System Application at the Jayapura Regency BPKAD. Furthermore, the originality of this research can be found in its contribution to the existing literature.